MARKOV CLUSTERING FOR PORTFOLIO CONSTRUCTION UNDER STOCHASTIC ENVIRONMENT - Handika, Tri; Lubis, Arief Wibisono (UG Journal, 2014)
Until recently there were still many new investors andfinancial consultants whoface dificulties in stocks portfolio construction, both in terms of selection anddeciding how large portion ofeach asset in the portfolio. It takes relatively longertime and hence they constantly strive to achieve faster portfolio constructionbecause timely information can mean the difference between a deal struck ormissed, which translates to substantial profit or loss. This paper aims to analyzethe efficiency ofMarkov clustering processes for portfolio construction in order tospeed up assets selection based on correlation principle. Furthermore, portfoliooptimization for selected assets will be achieved with Markovian modeldriven bya Brownian motion process under stochastic environment. We compare theperformance ofthe constructed portfolio to LQ45, Kompcisioo, and Bisnis2y indicesusing Sharpe Ratio, and the results show that it outperforms these benchmarkindices. Hence, investors might use Markov clustering technique in the stocksselection as an alternative since it is more efficient in terms oftime and in this caseproven to provide better reward to risk taken by the investors.